Status and Extension of the Geant4-DNA Dielectric Models for Application to Electron Transport - Kyriakou, Ioanna; Emfietzoglou, Dimitris; Incerti, Sebastien (Frontiers in Physics, 2022)
The development of accurate physics models that enable track structure simulations of electrons in liquid water medium over a wide energy range, from the eV to the MeV scale, is a subject of continuous efforts due to its importance (among other things) in theoretical studies of radiation quality for application in radiotherapy and radiation protection. A few years ago, the Geant4-DNA very low-energy extension of the Geant4 Monte Carlo code had offered to users an improved set of physics models for discrete electron transport below 10 keV. In this work we present refinements to this model set and its extension to energies up to 1 MeV. Preliminary comparisons against the existing Geant4-DNA physics models with respect to total and differential ionization cross sections of electrons in liquid water are reported and discussed.